Materiality in community energy innovation: A systematic literature review of hands-on material engagement in energy transition - Kuu-Park, Goeun; Kohtala, Cindy; Juntunen, Jouni K.; Hyysalo, Sampsa (Elsevier, 2024)
Collective and citizen-driven activities for energy transition have been thriving globally in recent decades. Community energy innovation (CEI) developed through hands-on engagement with materials has garnered increasing attention from the interdisciplinary energy research community. The recent scholarly discussion has highlighted the role of materiality and its relation to collective agency, inclusion, and approaches to participation. Accordingly, paying attention to materiality in CEI can clarify sociotechnical aspects of energy innovation which have been commonly understood through either solely a social or technical view. Furthermore, fostering citizens' take-up of renewable energy in more democratic ways is a prerequisite for accelerating the energy transition and is arguably best done via material, hands-on engagement. However, the focus on materiality, particularly hands-on material engagement, in research on community energy appears to be fragmented. Therefore, we conducted a systematic literature review to better understand how researchers understand and approach materiality and material engagement in CEI. The results of analyzing 36 papers highlight that materiality in CEI has been studied in interdisciplinary fields through diverse methods, and we identify four types of networks in which such innovation emerges. We also identify geographically dispersed and Do-It-Yourself enthusiast-led energy innovations which go beyond the existing understanding of CEI. More importantly, a network may change over time and place because of the configurational material nature of decentralized small-scale renewable energy technologies. However, studying materially-engaged CEI needs further efforts to integrate empirical data more centrally with the existing knowledge base and concretely define how materiality plays out in collective energy innovation.
Keywords: Materiality; Material engagement; Community innovation; Community energy; Renewable energy; fi=Tuotantotalous|en=Industrial Management|